A Potential Linking between Vitamin D and Adipose Metabolic Disorders. (19th February 2020) - Miao, Zhiguo; Wang, Shan; Wang, Yimin; Guo, Liping; Zhang, Jinzhou; Liu, Yang; Yang, Qiyuan
Abstract : Vitamin D has been discovered centuries ago, and current studies have focused on the biological effects of vitamin D on adipogenesis. Besides its role in calcium homeostasis and energy metabolism, vitamin D is also involved in the regulation of development and process of metabolic disorders. Adipose tissue is a major storage depot of vitamin D. This review summarized studies on the relationship between vitamin D and adipogenesis and furthermore focuses on adipose metabolic disorders. We reviewed the biological roles and functionalities of vitamin D, the correlation between vitamin D and adipose tissue, the effect of vitamin D on adipogenesis, and adipose metabolic diseases. Vitamin D is associated with adipogenesis, and vitamin D supplements can reduce the burden caused by metabolic diseases. The review provides new insights and basis for medical therapy on adipose metabolic diseases.